(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
The speciality rice of Assam, both “Joha”, (variety Kon) and pigmented rice (variety Chakhao) in whole and broken form were stored at ambient condition and dark for 180 days under four different packaging materials. The moisture content, crude fat and acid value together with the phenolic compound of rice were recorded during storage. The vacuum packaging was found to be the best method of packaging for both “Joha” rice and pigmented rice (both whole and broken). Retention of aroma in “Joha” rice was the maximum (very strong, ++++) under vacuum packaged condition up to 120 days, which decreased to strong (+++) for both vacuum packaged and aluminium foil bag packaged condition at 180 days. Microbial study indicated that bacterial infestation was the cause for spoilage of pigmented rice during storage.